Hidrološke raziskave ARSO na območju Bohinja - Bat, Marjan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
The Environmental Agency of the Republic of Slovenia (ARSO) performs hydrological measurements in the Bohinj region at the water gauging stations on the Sava Bohinjka, the Savica, the Bistrica, the Mostnica, and on Lake Bohinj. The summarized results of the observations are regularly published in Hydrological Yearbooks and are available to public. Within the water balance analyses the data on water discharges are harmonized with the data on precipitation and evapotranspiration. Two water tracing tests were made in the Bohinj region in order to clear up the established discordances. They show that, due to karstic bifurcation, the drainage area of the water gauging stations in the Bohinj region has to be treated as one unit as far as the water balance is concerned.
Keywords: Bohinj; površinske vode; vodotoki; hidrologija; vodna bilanca